2002
DOI: 10.1115/1.1493814
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Operating Point on the Pressure Fluctuations at the Blade Passage Frequency in the Volute of a Centrifugal Pump

Abstract: An experimental investigation is presented which analyzes the unsteady pressure distribution existing in the volute of a conventional centrifugal pump with a nondimensional specific speed of 0.48, for flow-rates from 0% to 160% of the best-efficiency point. For that purpose, pressure signals were obtained at 36 different locations along the volute casing by means of fast-response pressure transducers. Particular attention was paid to the pressure fluctuations at the blade passage frequency, regarding both ampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(54 citation statements)
references
References 7 publications
3
51
0
Order By: Relevance
“…A very satisfactory comparison between calculations and experimental results is presented (see Parrondo-Gayo et al [10]) Several others' works (Gu et al [11]; Muggli et al [12]; Cravero and Marini [13]) have shown good agreement between simulation and experimental results.…”
Section: Cfd In the Turbomachinerymentioning
confidence: 56%
“…A very satisfactory comparison between calculations and experimental results is presented (see Parrondo-Gayo et al [10]) Several others' works (Gu et al [11]; Muggli et al [12]; Cravero and Marini [13]) have shown good agreement between simulation and experimental results.…”
Section: Cfd In the Turbomachinerymentioning
confidence: 56%
“…The shape and location of the volute tongue also significantly affecting the pump performance such as the measurement done by Lipski [19]. Parrondo-Gayo et al [20] experiment with mounting of pressure transducers on front side of volute circumferentially around impeller outlet, found that pressure fluctuations and amplitudes are to be very dependent on both angular position and flow rate, maximum values corresponded to the tongue region for off-design conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, lots of numerical and experimental investigations have been carried out, and the fast Fourier transform (FFT) method has been proved to be the most powerful tool to unveil the frequency characteristics of pressure fluctuations. Yao et al [8] analysed both frequency domain and time-frequency domain in a double suction centrifugal pump based on fast Fourier transform (FFT) and time-frequency representation methods. Parrondo et al [9] also investigated the unsteady pressure distribution in a conventional centrifugal pump, and particular attention was paid on pressure fluctuations at blade passage frequency.…”
Section: Introductionmentioning
confidence: 99%